Role of Nuclear Receptors in Spontaneous and Recurrent Miscarriage - Julia Knabl; Aurelia Vattai; Brigitte Ziegelmüller; Nina Ditsch; Udo Jeschke (European Medical Journal, 2015)
Although early pregnancy loss is a common complication of human reproduction, a significant proportion of miscarriages still happen for unknown reasons. Nuclear receptors are key players in trophoblast invasion and metabolism; therefore, their agonists and ligands are a promising target for the prevention of miscarriage. This review gives an overview of the existing data and literature concerning the involvement of nuclear receptors in maintaining a viable pregnancy.